Ewolucja kompetencji Komitetu Praw Człowieka - Michalska, Anna (Wydział Prawa i Administracji UAM, 1996)
Pursuant to Art 40(4), following consideration of State's report, the Committee transmits to the State Parties "its reports, and such general comments as it may consider appropriate". The interpretation of this provision has met with great difficulties in the Committee and its practice has been largely blocked by the differences of opinion in the interpretation of opinion cited above. In recent years the Committee undertook a number of efforts to adopt a more evaluative approach towards State reports. Since the mid-eighties it has become a common practice for the Committee members to submit a quasiconcluding personal statement on the human rights situation in the State concerned. In 1992 the Committee started a new initiative by appointing Special Rapporteurs with the task of adopting comments on every State report. These comments were adopted by consensus and are formulated in rather general and cautious terms. Nevertheless, the sections on "principal subjects of concern" as well as the final "suggestions and recommendations" also point to specific human rights violations and developments. The fact that the Committee prefers to call these evaluations "comments" rather than "reports" as provided for in Art. 40(4) shows its careful step approach from "review" to "control". The individual communications procedure is concluded with "views" on the violation of the Covenant by the State Party. The Committee does not confine itself to the mere determination that the Covenant has been violated but it usually concludes the view with a statement on the resulting obligations of the State Party. The views adopted by the Committee are not binding under international law. The Optional Protocol does not provide any measures for supervising their enforcement and State Parties are not obligated to inform the Committee of the measures they have taken with regard to decided cases. In 1990 the Committee formalized this procedure by issuing a statement concerning measures to monitor compliance with its views. The Special Rapporteur for the Follow-Up of Views is appointed each year. This Rapporteur is entrusted to communicate with States Parties and victims of a violation and to make to the Committee recommendations on any further action. The guidelines for the preparation of State reports were supplemented with a section concerning actions in response to individual communications. The Annual Reports of the Committee contain information on the replies of States to the Special Rapporteur's requests.
Evolution of the competences of the Human Rights Committee